ROCKing cytokine secretion balance in human T cells. Issue 2 (April 2015) - Zanin-Zhorov, Alexandra; Waksal, Samuel D.
Highlights ROCK2 promotes IL-17 and IL-21 secretion in mice and humans. ROCK2 contributes to regulation of IFN-γ secretion in T cells from rheumatoid arthritis patients. IL-2 and IL-10 secretion are negatively regulated by ROCK2 under Th17-skewing activation.